Assessing the Format, Duration and Frequency of Interactive Game Programs in terms of Child Engagement and Motivation - Laura Daniusevičiūtė-Brazaitė (Lithuanian Sports University, 2022)
Background. Research has shown that musculoskeletal disorders were most commonly found in children aged 4 to 6 years (Daniusevičiūtė-Brazaitė et al., 2019). Therefore, if these negative trends continue, the growing health problems will pose a greater threat to human well-being and become a serious financial burden on the state and society. Currently, technologies are an integral part of everyday life, so the need for interactive games or animated programs cannot be doubted. Research (Lobel et al., 2016) showed that the use of play-based intervention for children significantly improves fine and visual motor performance. Hence, it is important to identify the possible factors to pre-school children's irregular posture formation. Methods. Thirty children (15 girls and 15 boys) aged 5.6 ± 0.6 years (mean ± SD) participated voluntarily in the study. Interview method was used as a questionnaire for preschool children to determine the level of children's physical activity, the characteristics of interactive animated educational gaming programs, their impact and motivation when engaging in game programs. Also the assessment of the biomechanical applicability of physical exercises was measured using an inclinometer and Myoton 3 system for muscle tone, elasticity and stiffness, as well as posture assessment. The methods were applied before and after the experiment. Results. All children liked the exercises of intercative animated program on the first (before) day of the study, and 98% answered on the last (after) day of the study. A greater proportion (67%) reported feeling excited when doing the exercises of the interactive animated program for the first time, whereas on the last day of the study, 48% reported feeling excited and 37% happy. Muscle stiffness scores increased on the last (post) day of the study. High measurement reliability was established for all muscle stiffness measurements. Conclusion. The exercises of the interactive animated game program were engaging - all the participants willingly performed the exercises and strong emotions such as excitement, surprise, fun/mischief prevailed during the exercises. The exercises of the interactive animated game program were performed correctly. The measured results of muscle frequency, elasticity and stiffness increased on the last day of the study. Keywords: preschool child, physical activity, engagement, motivation, interactive animated educational gaming program.